Pengaruh Corporate Social Responsibility (CSR) "Internet Baik" terhadap Citra Perusahaan Telkomsel - Adawiyah, Sa,diyah El Adawiyah El; Setyohartono, Bagas (CommLine, 2022)
The development of the digital world has made Telkomsel strive to present a CSR concept and became a role model in digital literacy education in Indonesia through the concept of Digital Citizenship Education (DCE). CSR can be applied to digital ecosystem users with several aspects, such as awareness of digital behavior, digital information access rights, digital safety, and digital content & creativity. The theory used in this research is CSR theory according to Carrol (2016) and Image Theory according to Philip Kotler in Gasing (2016). The research method used is quantitative research with descriptive quantitative research type and research methods using surveys. The instrument used in this study used a questionnaire with thirty-five statement items, which were given to 88 respondents from 720 populations using a simple random sampling system. The data collected during the study was conducted and processed using SPSS version 24 for accurate calculations. The results showed that there is an influence between the “Internet Baik” CSR program on Telkomsel's corporate image with a coefficient determination (R2) is 0.518. The coefficient determination shows that it has a enough positive effect but a certain correlation between the CSR Internet Baik program carried out by the Telkomsel. This result shows that Telkomsel's Internet Baik CSR program can make society more positive in the digital world.Keyword : Corporate Social Responsibility (CSR), Telkomsel, Image.